UPAYA MENINGKATKAN SOFT SKILL MAHASISWA MELALUI PEMBELAJARAN BERBASIS PROJECT DALAM MATA KULIAH BUSINESS PRACTICE - murtianingsih, murtianingsih (LP2M Institut Teknologi dan Bisnis Asia Malang, 2018)
The School of Economics of Asia is one of the universities that runs the education system. In the implementation of education system in STIE ASIA Malang using competency-based curriculum. Changes in global conditions with competition, job requirements and strategic change. STIE ASIA as one of the universities in Indonesia where the results of a review of the curriculum offered to be able to compete with the strength of the work force of the ASEAN Economic Community (MEA) that has been implemented since January 1, 2016. With the orientation on the needs and relevance of the user then applied courses that are part of the local-based curriculum project